Impact of Social Customer Relationship Management on Customer Retention of Islamic banks in Kuwait: The Mediating Role of Customer Empowerment - Faraj Mazyed Aldaihani; Noor Azman Bin Ali (International Journal of Supply Chain Management, 2020)
In order to investigate the impact of social customer relationship management on customer retention through customer empowerment, this research paper was took place using a sample of social media users who were customers of Islamic banks in Kuwait. An online survey-founded questionnaire was conducted to gather data. A total of 600 questionnaires were distributed to participants in this study and 417 questionnaires were returned. On the basis of IBM SPSS 24 and IBM AMOS 22, data analysis confirmed that customer empowerment significantly mediated the effect of social CRM on customer retention. That is, social CRM was found to have a significant effect on customer empowerment and customer retention and indicated that customer empowerment had a significant influence on customer retention. Consequently, it was concluded that customer empowerment as a key pillar of social CRM positively effectuates customer outcomes such as customer retention.